2011
DOI: 10.1155/2011/824962
|View full text |Cite
|
Sign up to set email alerts
|

Modulation and Interaction of Immune‐Associated Parameters with Antioxidant in the Immunocytes of Crab Scylla paramamosain Challenged with Lipopolysaccharides

Abstract: Invertebrates are dependent on cellular and humoral immune defences against microbial infection. Scylla paramamosain is an important commercial species, but the fundamental knowledge on its immune defense related to the antioxidant and immune-associated reactions is still lacking. The study was to differentiate the responses of immune-associated parameters of haemolymph components in S. paramamosain when challenged with bacterial lipopolysaccharides (LPSs). The immunostimulating effects of LPS in crab by trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 70 publications
3
19
2
Order By: Relevance
“…Their responses suggested that many immune-associated parameters could be modulated and interrelated with the influence of antioxidants. Our results indicated that the NOS mRNA transcripts had most significant induction from 24 h to 48 h, that were a little different from the report from Gopalakrishnan et al [36], which showed LPSs injection also stimulated an increased level of nitric oxide, reaching the highest NO content during 6 he12 h time period. So NOS expression level showed significantly up-regulated after LPS injection, demonstrating that the immune system may intensify in S. paramamosain defense against to LPS stimulation [37].…”
Section: Discussioncontrasting
confidence: 99%
“…Their responses suggested that many immune-associated parameters could be modulated and interrelated with the influence of antioxidants. Our results indicated that the NOS mRNA transcripts had most significant induction from 24 h to 48 h, that were a little different from the report from Gopalakrishnan et al [36], which showed LPSs injection also stimulated an increased level of nitric oxide, reaching the highest NO content during 6 he12 h time period. So NOS expression level showed significantly up-regulated after LPS injection, demonstrating that the immune system may intensify in S. paramamosain defense against to LPS stimulation [37].…”
Section: Discussioncontrasting
confidence: 99%
“…The recovery of the number of circulating hemocytes occurs because of the production or release of immature hemocytes from hematopoietic tissue (Sequeira et al 1996;van de Braak et al 2002;Söderhäll 2003). Previous studies have also confirmed that S. paramamosain exhibited increased PO activity when challenged with LPS at 0.1 and 0.5 mg/kg doses (Gopalakrishnan et al 2011). In this study, the PO activity in crabs challenged with LPS increased significantly at 2 and 6 hpi.…”
Section: Discussionsupporting
confidence: 64%
“…The immune defenses in crustaceans largely rely on cellular and humoral defenses (Johansson and Söderhäll 1989). Here, the THCs were restored to their original levels 6 h after injection, and the results indicate that LPS at a dose of 0.05 mg/kg was less toxic to S. paramamosain compared with that at 0.5 mg/kg (Gopalakrishnan et al 2011). Here, the THCs were restored to their original levels 6 h after injection, and the results indicate that LPS at a dose of 0.05 mg/kg was less toxic to S. paramamosain compared with that at 0.5 mg/kg (Gopalakrishnan et al 2011).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations